An Analytical Study of the Japanese Language Education System in Sri Lanka: Strategies for Designing Courses and Training Teachers - Punchi Banda, S.M. (A thesis submitted for the Degree of Master of Arts, 1999)
During the past decade the numbers learning Japanese language had been progressively increasing in Colombo and outstations. However, teacher-training programs are hardly undertaken in Sri Lanka though 37 government funded institutions and 24 private institutes conduct Japanese language classes. A multi-paradigmatic approach was adopted in this study. Accordingly, 4 questionnaires were administered in addition to collecting data through participant observation in 3 districts covering 266 learners, 134 students who had n o t chosen Japanese as an o p t i o n a l s u b j e c t , and 2 4 teachers (both Sri Lankan and the Japanese) answered questionnaires. Consequently, 6 major elements were identified for training programs. Finally, the author designed 3 types of course modules pertinent to the present situation of Sri Lankan teachers, incorporating different goals, objectives, syllabi and curricula based on beliefs of learners and teachers of Japanese.